Pendampingan Edukasi Hukum Korban Kecelakaan bagi Anak-Anak Pelajar di Indramayu - Abdul Gofur (Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
This community service activity aims to improve legal understanding, awareness of victims' rights, and orderly traffic behavior. The methods used are outreach and education. The results of the mentoring activities indicate an increase in understanding within a legally aware environment. This activity not only provides practical legal knowledge but also fosters social empathy and a sense of justice in students, as the younger generation plays a vital role in building a legal culture in society. Therefore, this mentoring program is expected to become a model for child legal empowerment in other regions, while also strengthening the legal protection system for accident victims